Analysis of the activity and safety of weekly low‐dose bevacizumab‐based regimens in heavily pretreated patients with metastatic breast cancer. Issue 5 (25th March 2018) - Zhai, Xiaoyu; Hong, Ruoxi; Fan, Ying; Yuan, Peng; Wang, Jiayu; Sang, Die; Chen, Junlin; Zhao, Chunying; Ou, Kaiping; Ma, Fei; Xu, Binghe
Abstract : Background: Currently, there are no standard regimens for metastatic breast cancer patients (MBC) who have failed ≥ 3 chemotherapy treatments. The aim of this study was to assess whether weekly low‐dose bevacizumab‐based regimens were well tolerated and would improve efficacy in MBC patients who had failed numerous therapies. Methods: Seventeen patients with MBC who were heavily pretreated with a median of five regimens of therapy (range 1–10) between 2012 and 2016 were included in the analysis. Bevacizumab was administered at a dose of 100 mg intravenously once a week combined with one or two types of chemotherapeutic drugs until confirmed disease progression or an intolerable adverse event was observed. Patient characteristics, objective response rate, clinical benefit rate, progression‐free survival, and toxicity were assessed. Results: All 17 patients had been pretreated with taxane‐based and anthracycline‐based chemotherapy. Weekly low‐dose bevacizumab combined with one or two types of chemotherapeutic drugs, which had usually not been previously used (e.g. etoposide, irinotecan, pemetrexed, methotrexate, and nab‐paclitaxel), was administered. Three patients achieved a partial response, while one had stable disease for > 24 weeks, and the clinical benefit rate was 23.5%. Median progression‐free survival was 3.4 months (95% confidence interval 2.0–4.8). The most common hematological adverse events were neutropenia, anemia, and thrombocytopenia. Bevacizumab‐related adverse events included grade 1 bleeding (17.6%) and grade 2 hypertension (5.9%). Conclusions: Weekly low‐dose bevacizumab combined with chemotherapy shows a relatively favorable clinical response and tolerable toxicity, providing a feasible option for heavily pretreated MBC patients.